Evaluasi Kinerja Pemasok dengan Menggunakan Metode Analytic Hierarchy Process pada Apotek Sehat Farma - , ARDIAN PERDANA KUSUMA; , Drs. Pangestu Subagyo, M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Government program, Jaminan Kesehatan Nasional (JKN), will be effectively conducted starting January 1st, 2014. The program is targeting 70% of Indonesia population to participate in social insurance. Jaminan Kesehatan Nasional (JKN) will be run by BPJS Kesehatan. PT Askes was appointed by the government to be BPJS Kesehatan. With the transformation of PT Askes to be BPJS Kesehatan, the pharmacies that serve the current Askes members, will also serve all participants of social insurance later. The demand of medicine is estimated to increase as the customers from all social insurance members are served by those pharamcies. This makes those pharmacies must improve the quality of service and quality of medicine. In order to improve the quality, those pharmacies should manage the suppliers. Supplier management can be applied by evaluating the supplier performance. Pharmacies should conduct periodic evaluation to ensure those suppliers are in accordance with the standards prescribed by the pharmacies. The supplier evaluation is also useful for suppliers to maintain and improve their performance, so the coorperation can continue for a long time. Supplier evaluation can be used also to be the reference for pharmacies to decide the appropriate medicine suppliers to corporate in the future. This research was conducted at a pharmacy that served Askes members, Apotek Sehat Farma. Analytic Hierarchy Process was used in this supplier evaluation research. The purpose of this research is to determine the ranking of the suppliers based on their performaces. There are four criterias being used in this research in order to evaluate suppliers performace, which are price, quality, delivery, and service. Based on data analysis using Analytic Hierarchy Process, Apotek Medika Farma has the best performance with the weight rate0.300. Quality is the most important criteria for assessing the performance of suppliers with the weight rate 0.471.